Pembinaan hubungan di antara guru dengan pelajar - Mohd. Noor, Ahmad Firdaus (Politeknik, Engku Omar, Ipoh, Perak, 2016)
This article explains the relationship between teachers and students. The elements of a healthy relationship based on intimacy, safely and trustworthy are emphasised in this discussion. This topic has put emphasis on the theory of effective quality relationship as its theoretical perspective, models of social supports, and the theory of self-determination. To conclude, a few guidelines suggested by scholars in education have been inserted together with the discussion to analyse the practical aspects and the development of teacher-students relationship that can be useful to all educators.